USE OF THE TREND-FACTOR MODEL TO IMPROVE THE ACCURACY FORECASTS - Irina V. Orlova; Viktor B. Turundaevsky (Статистика и экономика, 2016)
In this paper we propose a method toimprove the accuracy of the trend-factormodel on the assumption that the increasein endogenous variable-screens dependnot only on time but also deviations fromtheir trend of exogenous variables, provedby the corresponding formulas that reﬂect the structure of the dispersion, these remnants of the trend-factor model.